Energy efficient secure communication architecture for wireless sensor network. Issue 16 (7th July 2016) - Mondal, Satyajit; Mohanty, Sraban Kumar; Nandi, Sukumar
Abstract: The wireless sensor network (WSN) is more vulnerable than the wired network because it is relatively easy for an adversary to eavesdrop, insert, alter, and intercept the message communicated in the network. Sensor nodes have very limited power and memory. While designing the secure communication architectures, the main goal is to design energy and memory efficient protocols. Most of the well‐known communication architectures like TinySec, LLSP, and MiniSec compromise with the security issues because of energy and memory constraints of sensor nodes. In WSN, communication consumes more energy than computation. By minimizing communication overhead, the energy consumption can be reduced. We propose a new "energy efficient secure communication architecture" called EESCA for WSN, to make the communication secure. Along with authentication, confidentiality and integrity, the proposed architecture provides strong replay protection, and data freshness as permutation and substitution are used to generate massage authentication code. EESCA is robust against heavy packet loss because reset or resynchronization of counter is not required. The proposed scheme is energy efficient as the security packet overhead is reduced by 1 byte over the best‐known secure communication architectures. The efficacy of EESCA is shown through theoretical and experimental analysis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Our proposed "Energy efficient secure communication architecture" called EESCA, along with authentication, confidentiality, and integrity, provides strong replay protection and data freshness as permutation and substitution are used to generate massage authentication code. EESCA is also robust against heavy packet loss our scheme is energy efficient as the security packet overhead is reduced by 1 byte over the best‐known secure communication architectures.